Researching pronunciation learning strategies: An overview and a critical look - Pawlak, Mirosław; Szyszka, Magdalena (Studies in Second Language Learning and Teaching, 2018)
Disparate goals that learners might have in learning second or foreign language pronunciation and the scant classroom time that can be dedicated to teaching this target language subsystem dictate that learner autonomy is of vital importance in this case and adept use of pronunciation learning strategies (PLS) can be viewed as key to the development of this attribute. Surprisingly, research on these strategies is scarce, mainly focusing on the identification and classification of PLS, diverse instruments are used for data collection and the findings are inconclusive. The paper provides an overview of the available research on PLS with respect to their identification, learners’ preferences concerning their use, factors mediating the application of PLS, and the effects of strategies-based instruction in this area. An attempt is also made to assess research of this kind and to suggest how it could be taken forward to provide insights that would be of value to practitioners.